2012
DOI: 10.1136/tobaccocontrol-2012-050483
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nicotine delivery systems: regulatory and safety challenges: Singapore perspective

Abstract: Based on samples tested in this study, many contain misleading information on product ingredients. The results show poor consistency between actual nicotine content analysed on ENDS cartridges and the amount labelled. These findings raise safety and efficacy concerns for current and would-be recreational users or those trying to quit smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 9 publications
(11 reference statements)
2
64
0
Order By: Relevance
“…Nationally, calls to poison control centers attributable to accidental exposure to e-cigarettes have increased dramatically (161%-333%), mostly involving children who were exposed to the replacement cartridges and liquids containing nicotine. 78.79 by guest on May 12, 2018 http://circ.ahajournals.org/…”
Section: Nicotinementioning
confidence: 99%
See 2 more Smart Citations
“…Nationally, calls to poison control centers attributable to accidental exposure to e-cigarettes have increased dramatically (161%-333%), mostly involving children who were exposed to the replacement cartridges and liquids containing nicotine. 78.79 by guest on May 12, 2018 http://circ.ahajournals.org/…”
Section: Nicotinementioning
confidence: 99%
“…Rather than encouraging cessation, the tobacco industry could promote e-cigarettes as a way to circumvent clean indoor air policies, thereby promoting dual use to sell more conventional cigarettes. The industry could also steer e-cigarette users to combustible products and thereby increase rather than by guest on May 12, 2018 http://circ.ahajournals.org/ Downloaded from decrease nicotine and tobacco addiction. 125 E-cigarette manufacturers are spending millions of dollars and working with major lobbying firms to pass legislation or influence regulation to exempt e-cigarettes or carve out a special classification.…”
Section: It Is Important That the Relevant Government Agency Monitor mentioning
confidence: 99%
See 1 more Smart Citation
“…12 This potential for greater health risk is increased as e-cigarettes are not currently regulated and vary in content, with actual content sometimes differing from labeled content. [23][24][25] Forthcoming regulations from the US Food and Drug Administration (FDA) are likely to reduce these concerns, but it should also be acknowledged that nicotine itself may be harmful. The 2014 Surgeon General's Report notes the need for quantifying level of risk from long-term use of nicotine, especially if such use becomes more prevalent, 1 as appears to occur commonly with e-cigarettes, 26 despite being relatively rare with NRT.…”
mentioning
confidence: 99%
“…For example, a 2014 HSA study raised safety and efficacy concerns about using ENDS as safer alternatives to cigarettes or part of a cessation program, after it analysed the contents of confiscated ENDS. The study, which included 20 brands of ENDS, reported inconsistences in the labelling and the actual amount of nicotine in ENDS cartridges, as well as the predominant use of misleading information about ingredients on product labelling and packaging (Cheah et al 2014). The product ban similarly extends to advertising such products, both in print and electronic media.…”
mentioning
confidence: 99%